Method for freeze-drying hydrogel composition, and freeze-dried hydrogel composition

JP2022171602A5Inactive Publication Date: 2025-02-28UPM KYMMENE OYJ
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2022071937
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-04-30
Filing Date
2022-04-25
Publication Date
2025-02-28
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Cellulose nanofibril and hydrogel compositions face challenges in dehydration and drying processes, as they are prone to structural damage and ice crystal formation, which can compromise the integrity and viability of biological materials encapsulated within.

Method used

A method involving freezing and drying of cellulose nanofibril-based hydrogel compositions with specific sugars and amino acids, followed by rehydration, to achieve a residual moisture content of 5% or less, preserving the structural integrity and biological functionality.

Benefits of technology

The method allows for stable long-term storage and transportation of biological materials, maintaining the structural integrity and viability of cells and other biological preparations, while minimizing ice crystal formation and membrane damage.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

To provide a method for freeze-drying a hydrogel composition, a freeze-dried hydrogel composition, a method for reconstituting a freeze-dried hydrogel composition, and a reconstituted hydrogel composition.SOLUTION: A method for freeze-drying a hydrogel composition comprises: providing the hydrogel composition, where the hydrogel composition comprises cellulose nanofibrils and / or cellulose nanocrystals, at least one saccharide, at least one amino acid, and biologics; and freeze-drying the hydrogel composition, thereby obtaining a freeze-dried hydrogel composition.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a method for lyophilizing a hydrogel composition, a lyophilized hydrogel composition, a method for reconstructing a lyophilized hydrogel composition, and a reconstructed hydrogel composition.

Background Art

[0002] Cellulose nanofibrils and hydrogels obtained therefrom have unique properties. For example, cells may be cultured in a cellulose nanofibril matrix in three-dimensional culture where the cells may grow as spheroids.

[0003] In some cases, it may be desirable to dehydrate and dry a cellulose nanofibril hydrogel, for example, one containing cells cultured therein. However, there may be challenges in handling cellulose nanofibrils and hydrogels obtained therefrom. For example, cellulose nanofibril hydrogels may not be easily dehydrated or lyophilized, and biological substances contained in the hydrogel may not withstand the process.

Summary of the Invention

[0004] A method for lyophilizing a hydrogel composition is disclosed. The method includes providing a hydrogel composition comprising cellulose nanofibrils and / or cellulose nanocrystals, at least one saccharide, at least one amino acid, and a biologic, and lyophilizing the hydrogel composition to obtain a lyophilized hydrogel composition.

[0005] A lyophilized hydrogel composition comprising cellulose nanofibrils and / or nanocrystals, at least one saccharide, at least one amino acid, and a biologic is disclosed. The residual moisture content of the lyophilized hydrogel composition may be 5 wt% or less.

[0006] A method for reconstituting a lyophilized hydrogel composition is disclosed. The method may include the step of adding water or an aqueous solution to the lyophilized hydrogel composition according to one or more embodiments described herein.

[0007] A reconstituted hydrogel composition comprising nanofibrils and / or nanocrystals, at least one sugar, at least one amino acid, and a biologic is disclosed.

[0008] The accompanying drawings, included to provide a further understanding of the embodiments and to constitute part of this specification, illustrate various embodiments. [Brief explanation of the drawing]

[0009] [Figure 1] The image shows SEM images of lyophilized NFC formulations that do not contain excipients (left) but contain 300 mM sucrose (center left), 300 mM trehalose (center right), 150 mM trehalose, and 333 mM glycine (right). A zoomed-in image of the same formulation is shown below. Arrows indicate examples of individual fibrous ribbons observed in formulations containing only trehalose or sucrose. Abbreviations: suc = sucrose, tre = trehalose, gly = glycine. [Figure 2] This shows the shear rate viscosity of a freeze-dried cake from an NFC formulation containing 300 mM sucrose (A), 150 mM trehalose, and 333 mM glycine (B), and 300 mM trehalose (B), but without biomolecules (control, D) (mean ± SD, n=3), before freeze-drying and after reconstitution. Abbreviation: FD = freeze-dried. [Figure 3] This shows the viscosity and reconstitution of nNFC (natural NFC) hydrogel FDed formulations. [Figure 4] This shows the size distribution of EVs derived from the PC3 cell line after FDing of the nNFC hydrogel formulation and enzymatic degradation of nNFCs. [Figure 5] This shows the amount of PNT2 cell line-derived EVs after FDing of nNFC preparations, nNFC reconstitution and enzymatic degradation, and EVs without nNFC hydrogel preparations. [Figure 6] Figure 6A shows a white solid cake of FDed NFC containing trehalose. Figure 6B shows a white solid cake of FDed NFC containing trehalose and glycine. Figure 6C shows a white solid cake of FDed NFC containing trehalose, glycine, and DMSO. Figure 6D shows an overall view of the white solid cake of FDed NFC. Figure 6E shows an SEM micrograph showing the porous aerogel structure of NFC when trehalose is used as an excipient. Figure 6F shows an SEM micrograph showing the ordered structure of nanofibers when trehalose is used as an excipient. [Figure 7] This shows the binding free energies of all sugars studied in molecular modeling systems, both with and without glycine molecules. [Figure 8A] The simulation results regarding the induced free energy for cellulose are shown. [Figure 8B] The simulation results regarding the induced free energy for cellulose are shown. [Figure 9A] This shows that the sugar-cellulose hydrogen bonds appear to have increased along with the amino acids. [Figure 9B] This shows that the sugar-cellulose hydrogen bonds appear to have increased along with the amino acids. [Figure 10] The FTIR spectrum of EV derived from the new FDed PC3 is shown. [Figure 11] The image shows FDed and reconstituted 3D cell spheroids stained with a live / dead dual staining kit. Enzyme activity is partially conserved (green), but the cell membrane is damaged and the cells are not completely viable (red). [Figure 12] A) and B) are scanning electron microscope (SEM) images showing the regular, porous structure of FDed NFC aerogel containing 3D cell spheroids, C) is a 3D cell spheroid encapsulated in NFC aerogel with preserved 3D structure and morphology, and D) is a scanning electron microscope (SEM) image showing a 3D cell spheroid encapsulated in NFC aerogel with intact cell membrane. The highly porous and interconnected pores of the NFC aerogel are clearly visible. [Figure 13] The cytoskeleton, F-actin (green), and cell nucleus (blue) of the positive control (left) and FDed and reconstituted 3D cell spheroids (right) are shown. [Figure 14] An example of a freeze-drying cycle used in cells is shown. [Modes for carrying out the invention]

[0010] A method for freeze-drying a hydrogel composition is disclosed. The method includes the steps of providing a hydrogel composition comprising cellulose nanofibrils and / or cellulose nanocrystals, at least one sugar, at least one amino acid, and a bioagent, and obtaining a freeze-dried hydrogel composition by freeze-drying the hydrogel composition.

[0011] A lyophilized hydrogel composition is also disclosed. The lyophilized hydrogel composition may contain cellulose nanofibrils and / or cellulose nanocrystals, at least one sugar, at least one amino acid, and a bioagent. The residual water content of the hydrogel composition may be 5 wt% or less.

[0012] A method for reconstituting a lyophilized hydrogel composition includes the step of adding water or an aqueous solution to the lyophilized hydrogel composition according to one or more embodiments described herein. Thus, a reconstituted hydrogel composition can be obtained.

[0013] Reconstituted hydrogel compositions are also disclosed. The reconstituted hydrogel may comprise nanofibrils and / or nanocrystals, at least one sugar, at least one amino acid, and a bioagent. The reconstituted hydrogel composition may be obtained by a method for reconstituting a lyophilized hydrogel composition according to one or more embodiments described herein.

[0014] By means of freeze-drying, the hydrogel composition and the biologic agent contained therein may be successfully dried and subsequently reconstituted. A low residual moisture content may be achieved, and a regular fiber matrix structure of the hydrogel composition may be obtained. The formation of ice crystals during freeze-drying may be reduced or avoided. Furthermore, during freeze-drying and reconstitution, the biologic agent contained in the hydrogel composition may be sufficiently preserved. For example, during freeze-drying and reconstitution, lipid structures such as cell membranes, exosome membranes, or other lipid bilayers may remain stable. As a further example, during freeze-drying and reconstitution, the cytoskeleton may be at least partially intact. When the cell membrane and its skeleton are not damaged, the cells may continue to survive and proliferate.

[0015] The freeze-dried hydrogel composition may be suitable for, for example, stable long-term storage and / or transportation. The freeze-dried hydrogel composition may be suitable for storage at room temperature, for example.

[0016] Without being bound by theory, at least one saccharide concentrating at the interface of water and cellulose nanofibrils and / or cellulose nanocrystals may help preserve the structure of the hydrogel during and after freeze-drying. At least one amino acid may increase the binding of at least one saccharide to cellulose nanofibrils and / or cellulose nanocrystals. Thus, at least one saccharide and at least one amino acid may function synergistically as cryoprotectants for the hydrogel structure and possibly the biologic agent contained in the structure.

[0017] A hydrogel composition containing cellulose nanofibrils may be referred to as a nanofibrillated cellulose hydrogel.

[0018] In the context of this specification, the terms "reconstitute" or "reconstitution" may be understood to refer to adding water and / or an aqueous solution to a lyophilized hydrogel composition such that the (residual) water content of the lyophilized hydrogel composition increases or returns to its original state prior to lyophilization. Upon reconstitution, the lyophilized hydrogel composition, e.g., an aerogel, may (again) form a hydrogel.

[0019] In the context of this specification, the term "cellulose nanofibril" may be understood to refer to nanofibrillated cellulose. These terms are used interchangeably.

[0020] Cellulose nanofibrils and / or cellulose nanocrystals may be prepared from plant-derived cellulose raw materials. The raw materials may be based on any plant material containing cellulose. The raw materials may also be obtained from specific bacterial fermentation processes. In one embodiment, the plant material is wood. The wood may be from conifers such as spruce, pine, fir, larch, Douglas fir, hemlock, or hardwoods such as birch, aspen, poplar, magnolia, eucalyptus, oak, beech, acacia, or a mixture of conifers and hardwoods. In one embodiment, the cellulose nanofibrils and / or cellulose nanocrystals are obtained from wood pulp. In one embodiment, the cellulose nanofibrils and / or cellulose nanocrystals are obtained from hardwood pulp. In one example, the hardwood is birch. In one embodiment, the cellulose nanofibrils and / or cellulose nanocrystals are obtained from softwood pulp.

[0021] Cellulose nanofibrils and / or cellulose nanocrystals may be produced from plant materials. In one example, cellulose nanofibrils and / or cellulose nanocrystals are obtained from non-substantial plant materials. In such cases, cellulose nanofibrils and / or cellulose nanocrystals may be obtained from secondary cell walls. One abundant source of such cellulose fibrils is wood fiber. The smallest cellulose components of plant-derived cellulose pulp, such as wood, consist of cellulose molecules, elementary fibrils, and microfibrils. Microfibril units are bundles of elementary fibrils brought about by physically coordinated coalescence as a mechanism to reduce the surface free energy.

[0022] Cellulose nanofibrils may be produced by homogenizing wood-derived fiber raw materials, or they may be made from chemical pulp. Cellulose fibers may be mechanically decomposed to produce fibrils with diameters in the nm range, such as 200 nm or less, or 50 nm or less, for example, 1 to 200 nm or 1 to 100 nm, and these fibrils may be dispersed in water. Cellulose nanofibrils may be type I cellulose. The fibrils may be reduced in size so that most of the fibrils have diameters in the range of 2 to 20 nm. Fibrils derived from secondary cell walls may be crystalline with a degree of crystallinity of at least 55%. Such fibrils may have different properties from fibrils derived from primary cell walls; for example, dehydration of fibrils derived from secondary cell walls may be more difficult.

[0023] In the context of this specification, the term “cellulose nanofibril” may refer to cellulose fibrils or fibril bundles separated from cellulosic fiber raw materials. These fibrils are characterized by a high aspect ratio (length / diameter), where the length may exceed 1 μm and the diameter generally remains less than 200 nm. The smallest fibrils are on the scale of so-called elementary fibrils, whose diameters generally range from 2 to 12 nm. The dimensions and size distribution of the fibrils may depend on the purification method and efficiency. Cellulosic nanofibrils are characterized as cellulosic materials, where the median length of the particles (fibrils or fibril bundles) is 50 μm or less, for example, in the range of 1 to 50 μm, and the particle size is less than 1 μm, for example, in the range of 2 to 500 nm. In the case of natural cellulose nanofibrils, in one embodiment, the average diameter of the fibrils is in the range of 5 to 100 nm, for example, in the range of 10 to 50 nm. Intact, unfibrillated microfibril units may be present in the nanofibril or hydrogel composition. In the context of this specification, the term "cellulose nanofibril" does not mean to include non-fibrous rod-shaped cellulose nanocrystals or whiskers.

[0024] The term "cellulose nanocrystals" may be understood in the context of this specification to refer to non-fibrous, rod-shaped cellulose nanocrystals. Cellulose nanocrystals are highly crystalline materials and may be called cellulose nanocrystals (CNC), cellulose nanocrystals (NCC), or cellulose nanowhiskers (CNW). Nanocrystals are rod-shaped, rigid, have a narrow size distribution, and are shorter than nanofibrils. Nanocrystals also have low viscosity and yield strength and typically do not have good water retention like nanofibrillated cellulose. Cellulose nanocrystals may have a width of about 2 to 30 nm. Cellulose nanocrystals may have a length of about 100 nm to several micrometers, or for example, 100 to 250 nm. These crystals can or may be obtained by acid hydrolysis of cellulose fibers. This may selectively decompose the amorphous regions of the cellulose fibers. In the initial stages of hydrolysis, the acid may be diffused into the amorphous portions of the cellulose fibers to hydrolyze the glycosidic bonds. After these, more easily accessible glycosidic bonds in the cellulose fibers may be hydrolyzed. Finally, hydrolysis may occur at the reducing end groups and on the surface of the nanocrystal.

[0025] Nomenclature related to cellulose nanofibrils is not currently uniform, and terminology may not be used consistently in the literature. For example, the terms cellulose nanofiber (CNF), nanofibrillary cellulose, nanofibrillated cellulose (NFC), nanocellulose, nanoscale fibrillated cellulose, microfibrillary cellulose, cellulose microfibrils, microfibrillated cellulose (MFC), and fibrillary cellulose may be used as synonyms for cellulose nanofibrils and / or nanofibrillated cellulose.

[0026] Therefore, a hydrogel containing cellulose nanofibrils may, for example, refer to a nanofibrillated cellulose (NFC) hydrogel as used herein.

[0027] Cellulose nanofibrils are characterized by their large specific surface area and strong ability to form hydrogen bonds. In aqueous dispersions, cellulose nanofibrils typically appear as a light or cloudy gel-like material. Depending on the fiber raw material, cellulose nanofibrils may also contain small amounts of other wood components such as hemicellulose or lignin. The amount depends on the plant source.

[0028] Different grades of cellulose nanofibrils may be classified based on three main properties: (i) size distribution, length, diameter, (ii) chemical composition, and (iii) rheological properties. Properties may be used in parallel to fully describe the grades. Examples of different grades include natural (or unmodified) cellulose nanofibrils, oxidized cellulose nanofibrils (high viscosity), oxidized cellulose nanofibrils (low viscosity), and carboxymethylated cellulose nanofibrils. Within these main grades, subgrades may also exist, e.g., very fibrillated and moderately fibrillated, highly and lowly substituted, and low and high viscosity. Fibrillation techniques and chemical pre-modification may affect the fibril size distribution. Typically, nonionic grades may have a wide fibril diameter (e.g., in the range of 10–100 nm or 10–50 nm), while chemically modified grades may have a narrow fibril diameter (e.g., in the range of 2–20 nm). Regarding the modification grade, the distribution of fibril dimensions may be narrower. Specific modifications, particularly TEMPO oxidation, may yield shorter fibrils.

[0029] Depending on the raw material source, such as hardwood (HW) pulp and softwood (SW) pulp, different polysaccharide compositions may exist in the final nanofibrillated product. Generally, nonionic grades are prepared from bleached birch pulp and may result in a high xylene content (25 wt%). Modified grades may be prepared from either HW or SW pulp. In such modified grades, hemicellulose may also be modified along with the cellulose domain. The modification may be heterogeneous, meaning that some parts may be more modified than others. Therefore, detailed chemical analysis may not be possible—the modified product is typically a complex mixture of different polysaccharide structures.

[0030] In an aqueous environment, dispersions of cellulose nanofibrils may form viscoelastic hydrogel networks. The gel may form intertwined fibrils dispersed and hydrated at relatively low concentrations, e.g., 0.05–0.2% (w / w). The viscoelasticity of NFC hydrogels may be characterized, for example, by dynamic vibrational rheology measurements. Cellulose nanofibril hydrogels may exhibit characteristic rheological properties. For example, they may be shear-thinning or pseudoplastic materials, meaning their viscosity depends on the rate (or force) at which the material deforms. When viscosity is measured with a rotational rheometer, shear-thinning behavior is observed as a decrease in viscosity with increasing shear rate. Hydrogels exhibit plastic behavior, meaning that a certain shear stress (force) is required before the material begins to flow easily. This critical shear stress is often called the yield stress. The yield stress can be determined by the steady-state flow curve measured with a stress-controlled rheometer. When viscosity is plotted as a function of added shear stress, a dramatic decrease in viscosity is observed after exceeding the critical shear stress. Zero shear viscosity and yield stress may be the most important rheological parameters for explaining the suspension forces of a material. These two parameters may distinguish different grades very clearly, and thus grades may be classified accordingly.

[0031] The dimensions of the fibrils or fibril bundles may depend on the raw materials and the decomposition method. Mechanical decomposition of the cellulose raw material may be carried out using any suitable equipment such as refiners, grinders, pulverizers, homogenizers, colloids, friction grinders, pin mills, rotor-rotor dispersers, ultrasonic processors, microfluidizers and macrofluidizers or fluidinizer-type homogenizers. The decomposition process may be carried out under conditions in which sufficient water is present to prevent the formation of bonds between fibers.

[0032] In one example, disassembly is carried out by using a disperser having at least one rotor, blade, or similar moving mechanical component, such as a rotor-rotor disperser. An example of a rotor-rotor disperser is the Atrex system.

[0033] Another example of equipment suitable for disassembly is a pin mill, such as a multi-peripheral pin mill. An example of such equipment is described in US6202946B1.

[0034] In one embodiment, decomposition is carried out by using a homogenizer.

[0035] In the context of this specification, the term “fibrillation” may generally refer to the separation of cellulose fibrils from fibers or fibrous fragments by mechanically breaking down the fibrous material through an operation performed on the particles. This operation may be based on a variety of effects, such as grinding, crushing, or shearing, or a combination thereof, or another corresponding operation that reduces particle size. The energy required for the refining operation is generally expressed in units of energy per unit volume of the raw material being processed, for example, kWh / kg, MWh / ton, or a proportional unit. The terms “decomposition” or “decomposition treatment” may be used interchangeably with “fibrillation.” The fibrous material dispersion undergoing fibrillation may be a mixture of fibrous material and water (or aqueous solution), and is also referred to herein as “pulp.” A dispersion of fibrous material may generally refer to whole fibers, parts (fragments) separated from them, fibril bundles, or fibrils mixed with water. Typically, an aqueous fibrous material dispersion is a mixture of such elements, and the ratio between the components depends on the degree or stage of processing, for example, the number of times the processing of the same batch of fibrous material is performed or "passed through".

[0036] The decomposed fibrous cellulose raw material may be modified or unmodified. Modified fibrous raw material means that the fibers have been affected by a modification treatment so that the cellulose nanofibrils can be more easily separated from the fibers. The modification may be performed on the fibrous cellulose raw material existing as a suspension in a liquid, for example, as pulp.

[0037] The modification treatment of the fibers may be chemical or physical. In chemical modification, the chemical structure of the cellulose molecule is altered by a chemical reaction (derivativeation of cellulose), for example, the length of the cellulose molecule is unaffected, but functional groups are added to the β-D-glucopyranose units of the polymer. Chemical modification of cellulose may occur with a specific degree of conversion depending on the dosage of reactants and reaction conditions, and is often incomplete, so that the cellulose remains in solid form as fibrils and is insoluble in water. In physical modification, anions, cationic or nonionic substances, or any combination thereof, may be physically adsorbed onto the cellulose surface. The modification treatment may also be enzymatic. Cellulose in the fibers may be particularly ionically charged after modification, as the ionic charge of cellulose may weaken the internal bonds of the fibers and promote subsequent decomposition into cellulose nanofibrils. The ionic charge may be achieved by chemical or physical modification of cellulose. The fibers may have a higher anionic or cationic charge after modification compared to the starting material. Chemical modification methods commonly used to generate anionic charges include oxidation, sulfonation, and carboxymethylation, in which hydroxyl groups are oxidized to aldehyde and carboxyl groups. Cationic charges may then be chemically generated by cationization, which involves bonding cationic groups, such as quaternary ammonium groups, to cellulose.

[0038] Cellulose may be oxidized. In the oxidation of cellulose, the primary hydroxyl groups of cellulose may be catalytically oxidized by heterocyclic nitroxyl compounds, such as the 2,2,6,6-tetramethylpiperidinyl-1-oxy free radical commonly known as "TEMPO". At least some primary hydroxyl groups (C6-hydroxyl groups) of cellulosic β-D-glucopyranose units may be selectively oxidized to carboxyl groups. Some aldehyde groups may also be formed with primary hydroxyl groups. Cellulose may be oxidized to a level in which the carboxylic acid content in the oxidized cellulose is in the range of 0.6–1.4 mmol COOH / g pulp or 0.8–1.2 mmol COOH / g pulp, for example, 1.0–1.2 mmol COOH / g, as determined by conductivity titration. The oxidized cellulose fibers thus obtained may, upon decomposition in water, provide a stable, transparent dispersion of individualized cellulose fibrils, for example, with a width of 3–5 nm.

[0039] Cellulose nanofibrils may also be characterized by their average diameter (or width), or by their viscosity and average diameter, such as Brookfield viscosity or zero shear viscosity. In one embodiment, the cellulose nanofibrils have a number-average diameter of fibrils in the range of 1 to 100 nm. In one embodiment, the cellulose nanofibrils have a number-average diameter of fibrils in the range of 1 to 50 nm. In one embodiment, the cellulose nanofibrils have a number-average diameter of fibrils in the range of 2 to 15 nm, such as TEMPO-oxidized nanofibrillated cellulose. The diameter of one or more fibrils may be determined using several techniques, such as microscopic examination. The thickness and width distribution of fibrils may be measured by image analysis of images from a field emission scanning electron microscope (FE-SEM), a transmission electron microscope (TEM) such as a cryo-TEM, or an atomic force microscope (AFM). Generally, AFM and TEM are suitable for cellulose nanofibril grades with a narrow fibril diameter distribution.

[0040] The viscosity of cellulose nanofibril or hydrogel compositions may be measured by rheometer. In one example, the rheometer viscosity of a nanofibrillated cellulose dispersion is measured at 22°C using a stress-controlled rotational rheometer (AR-G2, TA Instruments, UK) with a narrow-gap vane shape (vane having a diameter of 28 mm and a length of 42 mm) in a cylindrical sample cup with a diameter of 30 mm. After placing the sample in the rheometer, the sample is allowed to stand for 5 minutes before starting the measurement. Steady-state viscosity is measured by measuring the shear stress (proportional to the applied torque) and shear rate (proportional to the angular velocity) as the shear stress and shear rate are gradually increased. The viscosity reported at a specific shear stress (= shear stress / shear rate) is recorded after reaching a certain shear rate, or after a maximum of 2 minutes. The measurement stops when the shear rate exceeds 1000 s⁻¹. This method may also be used to determine the zero shear viscosity.

[0041] For example, when dispersed in water, cellulose nanofibrils provide a zero shear viscosity (a "plateau" of constant viscosity at small shear stresses) in the range of 1,000 to 100,000 Pa·s, e.g., 5,000 to 50,000 Pa·s, as determined by a rotational rheometer at a concentration (consistency) of 0.5 wt% (w / w) in an aqueous medium, and a yield stress (the shear stress at which shear viscosity reduction begins) in the range of 1 to 50 Pa, e.g., 3 to 15 Pa.

[0042] When dispersed in water at a concentration of 0.5 w% cellulose nanofibrils, they may have a storage modulus in the range of 0.3 to 50 Pa. For example, when dispersed in water at a concentration of 0.5 w% cellulose nanofibrils, the storage modulus may be in the range of 1 to 20 Pa or 2 to 10 Pa.

[0043] Turbidity is the cloudiness or haze of a fluid caused by individual particles (completely suspended or dissolved solids) that are generally invisible to the naked eye. There are several practical methods for measuring turbidity, but the most direct method is to measure the attenuation of light (i.e., the decrease in intensity) as it passes through a water column of a sample. The Jackson candle method (unit: Jackson turbidity units or JTU), which is used as an alternative, is essentially an inverse measure of the length of a water column required to completely obscure a candle flame as seen through it.

[0044] Turbidity may be measured quantitatively using an optical turbidimeter. Several commercially available turbidimeters are available for quantitative measurement of turbidity. In this case, a method based on nephelometry is used. The unit of turbidity from a calibrated turbidimeter is called the nephelometry turbidity unit (NTU). The measuring device (turbidimeter) is calibrated and controlled with a standard calibration sample, and then the turbidity of a diluted NFC sample is measured. In the turbidity measurement method, a nanofibrillated cellulose sample may be diluted in water to a concentration below the gelation point of nanofibrillated cellulose, and the turbidity of the diluted sample may be measured. The concentration at which the turbidity of the cellulose nanofibril sample is measured may be 0.1%. A HACH P2100 turbidimeter with a 50 ml measuring container may be used for turbidity measurement. The dried cellulose nanofibril sample may be measured, and 0.5 g of the sample calculated as the dried sample may be placed in a measuring container. Alternatively, 500 g of tap water may be added to the measuring container and shaken vigorously for approximately 30 seconds. Without delay, the aqueous mixture may be divided into five measuring containers, which may be inserted into a turbidimeter. Three measurements may be performed for each container. The mean and standard deviation may be calculated from the obtained results, and the final result may be obtained in NTU units.

[0045] One way to characterize cellulose nanofibrils or hydrogels containing them is to define both viscosity and turbidity. Low turbidity may correlate with small fibril size, e.g., small diameter, due to insufficient light scattering by small fibrils. Generally, as the degree of fibrilization increases, viscosity increases while turbidity decreases. However, this may only occur up to a certain point in time. If fibrilization continues further, the fibrils may eventually begin to break down and become unable to form a strong network. Therefore, from this point onward, both turbidity and viscosity may begin to decrease.

[0046] In one example, the turbidity of anionic cellulose nanofibrils or hydrogels containing them is less than 90 NTU, e.g., 3–90 NTU, e.g., 5–60, e.g., 8–40, and is measured at a concentration of 0.1% (w / w) in an aqueous medium by turbidimetry. In another example, the turbidity of natural cellulose nanofibrils or hydrogels containing them is greater than 200 NTU, e.g., 10–220 NTU, e.g., 20–200, e.g., 50–200, and may be measured at a concentration of 0.1% (w / w) in an aqueous medium by turbidimetry. To characterize the cellulose nanofibrils or hydrogels containing them, these turbidity ranges may be combined with the viscosity range of the cellulose nanofibrils or hydrogels containing them.

[0047] The hydrogel composition may be provided, for example, by mixing a hydrogel containing cellulose nanofibrils and / or cellulose nanocrystals with a solution containing at least one sugar and at least one amino acid. The bioagent may be mixed with the hydrogel and solution, or may be contained within the hydrogel, for example (e.g., as a result of culturing the bioagent in the hydrogel).

[0048] The hydrogel composition (i.e., the hydrogel composition before lyophilization) may contain cell culture medium. The method may further include the step of removing at least partially the cell culture medium from the hydrogel composition and replacing the cell culture medium with a solution containing at least one sugar and at least one amino acid before lyophilizing the hydrogel composition.

[0049] The content or concentration of at least one sugar in the hydrogel composition (before freeze-drying) may be in the range of 100 to 1000 mM. Alternatively or additionally, the content or concentration may be in the range of 150 to 500 mM. In embodiments in which at least one sugar comprises two or more sugars, the total (i.e., combined) content or concentration of the two or more sugars may be in the range of 100 to 1000 mM or 150 to 500 mM.

[0050] The content or concentration of at least one amino acid in the hydrogel composition (before freeze-drying) may be in the range of 50 to 700 mM. Alternatively or additionally, the content or concentration may be in the range of 100 to 500 mM. In embodiments in which at least one amino acid comprises two or more amino acids, the total (i.e., combined) content or concentration of the two or more amino acids may be in the range of 50 to 700 mM or 100 to 500 mM.

[0051] The concentration and consistency of the hydrogel composition may be, for example, 2 wt% or less, 1 wt% or less, or 0.2 to 2 wt%.

[0052] Cellulose nanofibrils may include or be natural, i.e., unmodified, cellulose nanofibrils.

[0053] In one embodiment, the cellulose nanofibril includes chemically modified cellulose nanofibrils, such as anionically modified cellulose nanofibrils. In one embodiment, the cellulose nanofibril is anionically modified cellulose nanofibril. In one embodiment, the anionically modified cellulose nanofibril is oxidized cellulose nanofibril. In one embodiment, the anionically modified cellulose nanofibril is sulfonated cellulose nanofibril. In one embodiment, the anionically modified cellulose nanofibril is carboxymethylated cellulose nanofibril.

[0054] Freeze-drying is a suitable preservation method for drying, for example, heat-sensitive biological products. Freeze-drying is widely used for the preservation of protein pharmaceuticals, vaccines, and other biological products. In the freeze-drying process, first, the hydrogel composition may be frozen below its glass transition (Tg') temperature in a freeze-drying chamber, which may be called the freezing step. Next, the pressure in the freeze-drying chamber may be reduced below the triple point of water, which may be called the primary drying step. Primary drying can result in the sublimation of the frozen water contained in the hydrogel composition. After primary drying, the hydrogel composition may be heated and the temperature slowly increased to further sublimate any unfrozen bound water, which may be called the secondary drying step. In other words, freeze-drying may include freezing, a primary drying step, and a secondary drying step of the hydrogel composition. The product of this process may be a dry solid formulation that can be stored in a refrigerator at room temperature and reconstituted by adding water or a suitable aqueous solution.

[0055] For example, the hydrogel composition may be frozen by lowering the temperature at which the hydrogel composition is held by 0.5 to 2°C / min until the hydrogel composition reaches a temperature lower than its glass transition temperature. In the primary drying stage, the pressure may be reduced to about 30 to 100 mTorr and the temperature may be increased to about -40 to -60°C. In the secondary drying stage, the temperature at which the hydrogel composition is held is increased by 0.5 to 2°C / min until the hydrogel composition reaches room temperature (e.g., about 20 to 25°C).

[0056] As a further example, the hydrogel composition may be frozen by lowering the temperature at which the hydrogel composition is held at a rate of 1°C / min until the hydrogel composition reaches approximately -55°C, and in the primary drying stage, the pressure may be reduced to approximately 100 mTorr and the temperature may be raised to approximately -40 to -50°C, and in the secondary drying stage, the temperature at which the hydrogel composition is held is raised at a rate of 1°C / min until the hydrogel composition reaches room temperature (e.g., approximately 20 to 25°C).

[0057] Freeze-drying may be performed by monitoring the residual water content and / or by controlling the temperature decrease with a temperature gradient, so that the temperature of the hydrogel composition is kept below the decay temperature of the hydrogel composition. Freeze-drying at a temperature higher than the decay temperature can lead to the decay of the hydrogel composition, while freeze-drying at a lower temperature can lead to longer freeze-drying cycles and thus more expensive freeze-drying cycles.

[0058] The glass transition temperature of the hydrogel composition may be measured before freeze-drying, and the freeze-drying cycle may be adjusted based on the measured glass transition temperature. Next, the temperature of the hydrogel composition may be maintained below its glass transition temperature.

[0059] Since the residual water content of the freeze-dried hydrogel composition may be relatively low, in at least some embodiments, the freeze-dried hydrogel composition may be considered to be an aerogel or an aerogel composition.

[0060] The residual moisture content of the lyophilized hydrogel composition may be, for example, 4 wt% or less, 2 wt% or less, 1 wt% or less, 0.2 to 3 wt%, or 0.5 to 2 wt%. The residual moisture content may include the residual moisture content of the bioagent in the lyophilized hydrogel composition. In other words, the residual moisture content of the lyophilized hydrogel composition may be the total residual moisture content of all components in the lyophilized hydrogel composition. Therefore, the residual moisture content may depend, for example, on the (relative) amount of the bioagent in the lyophilized hydrogel composition and / or on the properties of the bioagent. For example, cells may have a higher residual moisture content compared to, for example, the hydrogel portion of the lyophilized hydrogel composition. The residual moisture content may also depend, for example, on the content of at least one sugar and / or at least one amino acid in the lyophilized hydrogel composition.

[0061] The residual water content may be understood as the amount of water, for example, the amount of water bound to the lyophilized hydrogel composition that remains in the lyophilized hydrogel composition during and / or after the secondary drying stage of lyophilization. The residual water content may be determined by titration, for example, as described in the examples. Since water is removed during lyophilization, the amount of residual water may be important for the reconstruction of the lyophilized hydrogel composition, but it is preferable that there should not be a large amount of water that would damage the bioagent by forming ice crystals.

[0062] It may be a lyophilized hydrogel composition, a lyophilized aerogel, or a lyophilized aerogel composition.

[0063] At least one amino acid may be any suitable amino acid, such as naturally occurring amino acids and / or amino acids that make up proteins. At least one amino acid may be one or more of the following amino acids: glycine, arginine, histidine, lysine, aspartic acid, glutamic acid, serine, threonine, asparagine, glutamine, cysteine, selenocysteine, proline, alanine, isoleucine, leucine, methionine, phenylalanine, tryptophan, tyrosine, valine, or mixtures or combinations thereof.

[0064] At least one amino acid may be one or more of arginine, histidine, lysine, and / or mixtures or combinations thereof, which have positively charged side chains.

[0065] At least one amino acid may include one or more amino acids from aspartic acid, glutamic acid, and / or mixtures or combinations thereof, which have negatively charged side chains.

[0066] At least one amino acid may be one or more of the following amino acids having an uncharged side chain: serine, threonine, asparagine, glutamine, and / or mixtures or combinations thereof.

[0067] At least one amino acid may include one or more amino acids from glycine, cysteine, selenocysteine, proline, and / or mixtures or combinations thereof, or one or more of these.

[0068] At least one amino acid may be one or more of the following amino acids having a hydrophobic side chains: alanine, isoleucine, leucine, methionine, phenylalanine, tryptophan, tyrosine, valine, and / or mixtures or combinations thereof.

[0069] Any amino acid described herein may be an L-stereoisomer of the above amino acid.

[0070] At least one amino acid may include glycine, leucine, isoleucine, alanine, tryptophan, asparagine, glutamine, and / or mixtures or combinations thereof.

[0071] At least one amino acid may be glycine.

[0072] At least one amino acid may include tryptophan, asparagine, glutamine, and / or a mixture or combination thereof, or may be any one thereof.

[0073] At least one sugar may include at least one of disaccharides, trisaccharides, oligosaccharides, or mixtures or combinations thereof, or at least one of them.

[0074] At least one sugar may include at least one of disaccharides, trisaccharides, or mixtures or combinations thereof, or at least one of them.

[0075] In the context of this specification, the term “oligosaccharide” may be understood, in at least some embodiments, to refer to sugars containing 3 to 10 or 3 to 6 monosaccharide units (residues).

[0076] Examples of disaccharides include lactose, maltose, sucrose, cellobiose, trehalose, melibiose, and genthiobiose.

[0077] At least one sugar may include at least one of sucrose, trehalose, lactose, fructose, glucose, or a mixture or combination thereof, or at least one of them.

[0078] At least one sugar may include at least one of sucrose, trehalose, lactose, or a mixture or combination thereof, or at least one of them.

[0079] At least one sugar may be at least one non-reducing sugar, or may contain at least one non-reducing sugar. However, a reduction in sugars may also be considered.

[0080] The content of at least one sugar in the freeze-dried hydrogel composition may be in the range of 15 to 80 mol% or 30 to 70 mol%.

[0081] The content of at least one amino acid in the freeze-dried hydrogel composition may be in the range of 15 to 60 mol%.

[0082] The molar percentage (mol%) of at least one sugar and / or at least one amino acid in a lyophilized hydrogel composition may be understood as the molar percentage of all molecules (including water) in the lyophilized hydrogel composition, i.e., the amount of at least one sugar and / or at least one amino acid (moles) divided by the total amount of all components (molecules) in the lyophilized hydrogel composition.

[0083] The molar percentage (mol%) of at least one sugar and / or at least one amino acid in the lyophilized hydrogel composition may depend, for example, on the mol% of cellulose nanofibrils and / or cellulose nanocrystals in the lyophilized hydrogel composition.

[0084] The ratio of the content of at least one sugar to the content of at least one amino acid in the freeze-dried hydrogel composition and / or hydrogel composition may be in the range of 10:1 to 1:5. Additionally or alternatively, the ratio of the content of at least one sugar to the content of at least one amino acid may be in the range of 6:1 to 1:4.

[0085] Before lyophilization, various physicochemical properties of the hydrogel composition, such as pH, osmolarity, and / or ionic strength, may be controlled. For example, the osmolarity of the hydrogel composition may be adjusted or controlled to provide an osmolarity suitable for reconstitution, thereby, for example, increasing the stability of lipid structures or otherwise optimizing the properties of the lyophilized hydrogel composition. For example, HEPES, other suitable buffers, or other suitable components may be included in the hydrogel composition at concentrations such that the osmolarity of the hydrogel composition is suitable for reconstitution. Thus, the disruption of lipid structures such as cell membranes as a result of osmotic pressure can be avoided or reduced. If the osmolarity is appropriate, water (freshwater, free from additional components that affect osmolarity) may be added to the lyophilized hydrogel composition to reconstitute it.

[0086] The term “biological product” may be understood in the context of this specification to refer to a pharmaceutical product or biological product manufactured, extracted, or semi-synthesized from a biological source. A biological product may include vaccines, whole blood, blood components, allergens, somatic cells, materials for gene therapy, tissues, recombinant therapeutic proteins, and / or herbal medicines for cell therapy. A biological product may also include sugars, proteins, nucleic acids, or combinations thereof. A biological product may optionally or additionally include living cells or tissues. A biological product (or its precursors or components) may be isolated from a biological source (e.g., human, animal, plant, fungal, or microbial source).

[0087] The biological product may contain lipids, or may further contain lipids. For example, the biological product may contain a lipid membrane and / or a lipid bilayer.

[0088] The biologics may contain, or may be, cells such as spheroids, tissues or parts thereof, organoids, microorganisms, cellular components, extracellular vesicles such as exosomes, viral particles, and / or lipid nanoparticles and / or lipid-based transport means such as liposomes.

[0089] The cells may be, for example, 3D cell spheroids. However, various types of cells may be cultured and included in the hydrogel composition. The cells may be prokaryotic cells such as bacterial cells, or eukaryotic cells. Eukaryotic cells may be plant cells, yeast cells, or animal cells. Examples of eukaryotic cells include transplantable cells such as stem cells. The cells may be animal cells or human cells. The cells may be cultured cells. Examples of eukaryotic cells include transplantable cells such as stem cells, for example, totipotent, pluripotent, multipotent, minimally pluripotent, or unipotent cells.

[0090] Specific examples of cells include stem cells, undifferentiated cells, progenitor cells, fully differentiated cells, and / or combinations thereof. Stem cells are undifferentiated or partially differentiated cells that can regenerate themselves through cell division and can differentiate into multilineage cells. These cells may be classified as embryonic stem cells (ESCs), induced pluripotent stem cells (iPSCs), hematopoietic stem cells (HSCs), and adult stem cells, and may also be called tissue-specific or somatic stem cells. In the case of human embryonic stem cells, the cells may be from deposited cell lines or produced from unfertilized eggs, i.e., "parthenogenetic" eggs, or from parthenogenetically activated oocytes, so that the human embryo is not destroyed. The cells can be maintained and proliferated on or within a hydrogel without the use of animal or human-based chemicals that develop outside the cell. The cells may be uniformly dispersed on or within a hydrogel. Thus, examples of cells include stem cells, undifferentiated cells, progenitor cells, fully differentiated cells, and combinations thereof. In some examples, the cells include cell types selected from the group consisting of corneal stromal cells, keratinocytes, fibroblasts, epithelial cells, and combinations thereof. In some examples, the cells are selected from the group consisting of stem cells, progenitor cells, precursor cells, connective tissue cells, epithelial cells, muscle cells, nerve cells, endothelial cells, fibroblasts, keratinocytes, smooth muscle cells, stromal cells, mesenchymal cells, immune system cells, hematopoietic cells, hepatocytes, dendritic cells, hair follicle cells, and combinations thereof. The cells may also be genetically modified cells such as tumor or cancer cells, transgenic cells, cisgenic cells or knockout cells, or pathogenic cells. Such cells may be used, for example, in pharmaceutical research or therapy. In particular, stem cells may be used, for example, for therapeutic purposes provided to patients. However, various other types of cells may also be considered.

[0091] The tissue may be, for example, a biopsy-type tissue sample.

[0092] Extracellular vesicles (EVs) are vesicles produced by cells that function in various physiological events. Extracellular vesicles contain a phospholipid bilayer and may contain various compounds within the vesicle as cytosol. EVs may include, for example, microvesicles (secreted from the cell membrane, 100–1000 nm in diameter), exosomes (formed from within the cell, 50–120 nm in diameter), and / or apoptotic bodies (50–5000 nm in diameter, secreted from apoptotic cells). Depending on the biological task, EVs may differ in both structure (e.g., surface proteins) and cargo (e.g., RNA, proteins, gDNA).

[0093] Lipid nanoparticles are nanoparticles containing lipids. Lipid nanoparticles may be spherical. The average diameter of lipid nanoparticles is approximately 10 to 1000 nm. Lipid nanoparticles may contain a solid lipid core matrix which may be stabilized by an emulsifier.

[0094] Liposomes are spherical vesicles having at least one lipid bilayer. Liposomes can be used as a means of delivery for administering nutrients and pharmaceuticals, such as lipid nanoparticles in mRNA vaccines and DNA vaccines. Liposomes can be prepared by disrupting biological membranes (by techniques such as sonication). Liposomes may contain phospholipids, particularly phosphatidylcholine, but may also contain other lipids, such as egg yolk phosphatidylethanolamine. Major types of liposomes may include multilayer vesicles (MLVs) containing lipid bilayers of several lamellar phases, small monolayer vesicles (SUVs) containing one lipid bilayer, large monolayer vesicles (LUVs), spiral vesicles, and polyvesicle liposomes (one vesicle containing one or more smaller vesicles).

[0095] Lipid-based transport means such as lipid nanoparticles and / or liposomes, or extracellular vesicles, may further contain other components. For example, lipid-based transport means may contain proteins such as antibodies, DNA and / or RNA. However, a variety of other components may also be considered.

[0096] The aqueous solution may contain, for example, at least one of a buffer, physiological saline, cell culture medium, or a mixture or combination thereof, or at least one of them. The cell culture medium may be diluted. In this context, the term “diluted” may be understood to mean a cell culture medium that has been diluted further than the concentration immediately usable for cell culture (which may be considered to be 1x concentration). The aqueous solution may be biocompatible, i.e., compatible with the biologic.

[0097] For example, water may be added to the freeze-dried hydrogel composition first, followed by the addition of an aqueous solution such as cell culture medium or diluted cell culture medium.

[0098] When adding water and / or aqueous solutions and / or after adding them, the lyophilized hydrogel composition may be mechanically shaken, for example, by stirring. However, the mechanical shaking may be relatively gentle. The lyophilized hydrogel composition may absorb water and / or aqueous solutions very readily and may be relatively easily reconstituted. Therefore, reconstitution may be relatively gentle on cells.

[0099] In embodiments where the biopharmaceutical is a cell, tissue, or part thereof, organoids, microorganisms, or viral particles, for example, at least 5% of cells or viral particles, may be viable after reconstitution of the lyophilized hydrogel composition. Depending on various factors, for example, at least 10%, at least 20%, at least 30%, at least 40%, at least 50%, at least 60%, at least 70%, at least 80%, or at least 90% of cells or viral particles may be viable after reconstitution of the lyophilized hydrogel composition.

[0100] In embodiments where the bioagent is, for example, extracellular vesicles, at least 5% of the extracellular vesicles may be functionally and / or structurally preserved after reconstitution of the lyophilized hydrogel composition. Depending on various factors, for example, at least 10%, at least 20%, at least 30%, at least 40%, at least 50%, at least 60%, at least 70%, at least 80%, or at least 90% of the extracellular vesicles may be functionally and / or structurally preserved after reconstitution of the lyophilized hydrogel composition. The functionality of the extracellular vesicles may be determined, for example, using a cell viability assay.

[0101] The bioagent may be collected from the reconstituted hydrogel composition. Collection may be carried out, for example, by enzymatically digesting cellulose nanofibrils and / or cellulose nanocrystals and collecting the bioagent released from the reconstituted hydrogel composition.

[0102] The hydrogel composition, lyophilized hydrogel composition, and / or reconstituted hydrogel composition may be provided, for example, in cell plate format or on another solid-phase support.

[0103] Accordingly, solid-phase supports comprising hydrogel compositions, lyophilized hydrogel compositions and / or reconstituted hydrogel compositions are also disclosed. The solid-phase support may be a well plate, for example, a 24, 48, 96, 384 or 1536 well plate. Depending on the intended use, the solid-phase support may be, for example, a bag, bottle, column, syringe or glass vial. Such solid-phase supports may contain suitable biologics such as cells including spheroids, tissues or parts thereof, organoids, microorganisms, cellular components, extracellular vesicles such as exosomes, and / or viral particles. Such solid-phase supports may be readily available as cell models for cell culture, pharmaceutical and / or toxicity testing, or for other suitable purposes.

[0104] Various embodiments are described in detail.

[0105] The following description discloses several embodiments in detail so that those skilled in the art may utilize embodiments based on this disclosure. Not all steps or features of the embodiments are described in detail, as many steps or features are obvious to those skilled in the art based on this specification. Any examples are for illustrative purposes only and should not be construed as limiting.

[0106] Example 1 The roles of excipients such as sucrose in controlling residual moisture content in nNFC (natural nanofibrillated cellulose, i.e., natural nanofibrillated cellulose) hydrogels and lyophilized (FDed) nNFC formulations were reconstituted. The formulations used are as follows: 1,300 mM trehalose 2,300 mM sucrose 3.150 mM trehalose + 333 mM glycine 4. Control sample = 1.6% NFC hydrogel

[0107] The obtained SEM image is shown in Figure 1.

[0108] Figure 1 shows SEM images of lyophilized NFC formulations containing 300 mM sucrose (center left), 300 mM trehalose (center right), 150 mM trehalose, and 333 mM glycine (right), without excipients (left). Zoomed-in images of the same formulations are shown below. Arrows indicate examples of individual fibrous ribbons observed in formulations containing only trehalose or sucrose. Abbreviations: suc = sucrose, tre = trehalose, gly = glycine.

[0109] The measured viscosity of these formulations is shown in Figure 2.

[0110] Figure 2 shows the shear rate viscosity of lyophilized cakes from an NFC formulation containing 300 mM sucrose (A), 150 mM trehalose, and 333 mM glycine (B), and 300 mM trehalose (B), but without biomolecules (control, D) (mean ± SD, n=3), before lyophilization and after reconstitution. Abbreviations: FD = lyophilized.

[0111] Example 2: Freeze-drying of EVs derived from PC3 and PNT2 cell lines for long-term storage in an NFC matrix The formulations used for FDing of EVs from PC3 and PNT2 are as follows: Form 1: 200 mM Tre (trehalose), 75 mM GLY (glycine), 25 mM HEPES, 0.8% NFC, MQ water Form 2: 275mM TRE, 25mM HEPES, 0.8% NFC, MQ Form 3: 200 mM SUC, 75 mM GLY, 25 mM HEPES, 0.8% NFC, MQ Form 4: 275mM SUC, 25mM HEPES, 0.8% NFC, MQ Form 5: 200mM Tre, 75mM GLY, 25mM HEPES, MQ Form 6: 275mM TRE, 25mM HEPES, MQ Morphology 7: 200mM SUC, 75mM GLY, 25mM HEPES, MQ Morphology 8: 275mM SUC, 25mM HEPES, MQ Form 9: 0.8% NFC+ 300mM HEPES Morphology 10: 300mM HEPES

[0112] We were the first to study the reconstruction of nNFC hydrogels containing extracellular matrix (EVs). The obtained data are shown in Figure 3.

[0113] Figure 3 shows the viscosity and reconstitution of nNFC hydrogel FDed formulations. The formulations shown are as follows: Formation 1: 200mM Tre, 75mM GLY, 25mM HEPES, 0.8% NFC, MQ Form 2: 275mM TRE, 25mM HEPES, 0.8% NFC, MQ Form 3: 200 mM SUC, 75 mM GLY, 25 mM HEPES, 0.8% NFC, MQ Form 4: 275mM SUC, 25mM HEPES, 0.8% NFC, MQ

[0114] Figure 4 shows the size distribution of FDed EV after enzymatic degradation.

[0115] Figure 4 shows the size distribution of EVs derived from the PC3 cell line after FDing of nNFC hydrogel formulations and enzymatic degradation of nNFCs. The nNFC hydrogel formulations used are as follows: Form 2: 275mM TRE, 25mM HEPES, 0.8% NFC, MQ Form 4: 275mM SUC, 25mM HEPES, 0.8% NFC, MQ Form 6: 275mM TRE, 25mM HEPES, MQ Morphology 8: 275mM SUC, 25mM HEPES, MQ An example is EV derived from used storage PC3, stored at +4°C without FDing being performed.

[0116] Figure 5 shows the FDing and reconstitution of the nNFC hydrogel formulation, as well as the amount of particles after enzymatic degradation of nNFCs.

[0117] Figure 5 shows the amount of PNT2 cell line-derived EVs after FDing of nNFC preparations, enzymatic degradation of nNFCs, and FDing of EVs without nNFC hydrogel preparations. The preparations used are as follows: Formation 1: 200mM Tre, 75mM GLY, 25mM HEPES, 0.8% NFC, MQ Form 2: 275mM TRE, 25mM HEPES, 0.8% NFC, MQ Form 3: 200 mM SUC, 75 mM GLY, 25 mM HEPES, 0.8% NFC, MQ Form 4: 275mM SUC, 25mM HEPES, 0.8% NFC, MQ Form 5: 200mM Tre, 75mM GLY, 25mM HEPES, MQ Form 6: 275mM TRE, 25mM HEPES, MQ Morphology 7: 200mM SUC, 75mM GLY, 25mM HEPES, MQ Morphology 8: 275mM SUC, 25mM HEPES, MQ Form 9: 0.8% NFC+ 300mM HEPES Morphology 10: 300mM HEPES

[0118] Based on the data, FDing of nNFC formulations, including EVs, was considered successful when the residual moisture content was less than 1%.

[0119] Analysis using a nanoparticle tracking analyzer (NTA) was performed before lyophilization, after lyophilization, reconstitution, and enzymatic degradation of nNFCs.

[0120] NFC matrices containing excipients were successfully freeze-dried (FDed), and the formulations formed solid white cakes (Figures 6A-D). When the correct excipients were used in the formulation, the FDed cakes were successfully reconstituted with MQ-water. Samples containing trehalose or trehalose and glycine formed solid white cakes, while samples containing DMSO or glycerol disintegrated. FDed NFC samples containing trehalose formed a highly porous, continuous aerogel structure (Figure 6E), and upon further magnification, a regular fibrous structure was observed (Figure 6F). FDed NFC samples without excipients had an irregular fibrous structure and lacked a porous structure.

[0121] Table 1 shows the formulations and their residual water content. Residual water content can be controlled by adjusting the excipient formulation. This may be important when considering the application of FDing to EVs, single cells, and 3D cell spheroids, as biological samples may require a certain amount of water to be reconstituted, as shown in the literature.

[0122] [Table 1]

[0123] Example 3: Modeling of FDed NFC We studied the interactions between water, excipients, and NFCs using molecular dynamics (MD) simulations. By performing MD simulations, we investigated the dynamic behavior of the system and gained insights into specific mechanisms.

[0124] The simulation system was investigated to determine, for example, whether the binding strength between sugars and NFCs differed between monosaccharides and disaccharides. The introduction of glycine molecules was also investigated to see if it increased the interaction between sugars and the NFC surface. Molecules simulated on the NFC included trehalose, fructose, glucose, lactose, saccharose, and xylitol. All sugar molecules were simulated using an amorphous nanocellulose chain model.

[0125] We developed three planar simulation systems: one with a hydrophobic surface and another with a hydrophilic surface; crystalline cellulose to determine the bond free energy; and amorphous cellulose to determine the influence of biomolecules on water permeation. Excipients were added to the equilibrated aqueous system at random positions in the aqueous phase, at concentrations corresponding to the number of water molecules.

[0126] Three properties were of particular interest: the difference in free energy between the excipient and the cellulose layer, water penetration in the amorphous system, and the sugar chain exfoliation effect in the crystalline system, which was of interest during visualization. The difference in free energy was determined by generating the mean force potential from the partial density of the excipient via the gmx density. The difference in free energy was quantified using the more stable side of the cellulose surface. Water penetration was calculated using gmx select, with the average number of water molecules within 1 nm of the plane along the x and y axes formed by the centroid of the cellulose. The average number of glucose molecules in the same region was determined in the same way, except that it was divided by 6 using carbon molecules. Finally, a metric for chain exfoliation as a function of time was obtained by determining the RMSD of these individual chains using gmx rms on eight chains at the top and bottom of both crystalline cellulose layers. The results of excipient binding to the NFC surface were consistent between different cellulose surfaces.

[0127] In all cases, the effects of two different glycine concentrations on surface bonding and chain exfoliation were investigated. Specifically, for each sugar, three different simulations were performed at different sugar concentrations of 300, 225, and 200 mM. In these systems, the glycine concentration was set to 0, 75, or 100 mM, respectively. Therefore, the total concentration of all excipients was 300 mM in each simulation.

[0128] The results in Figure 7 show that all sugar molecules prefer to concentrate at the NFC-water interface. However, the bond strength differed between systems. The highest bond free energy was recorded for saccharose and lactose (without glycine). For fructose, glucose, and xylitol, slightly lower surface interactions were observed. It is difficult to estimate clear differences between systems because the resulting standard deviations overlap among the sugars. However, after the addition of glycine, the same trend in bond strength exists among the systems, with lactose, saccharose, and trehalose showing the strongest surface bonding. The addition of glycine did not increase the bond strength of glucose. However, in all other cases, the addition of glycine did not increase bonding. Based on the results, it is considered that the stronger bonding promoted by glycine is a very common outcome. Without glycine, the lowest bond free energy was -0.87 kJ / mol for xylitol, and the highest was -1.37 kJ / mol for saccharose. The molar percentages of xylitol and saccharose at the interface are given by the following formula: ΔG = RTln K D Based on estimations, values ​​of 59 mol% and 64% are obtained. This means that 59–64 mol% of the sugars present in the system are always bound to the NFC surface. When glycine is added to the saccharose system (100 mM), the mol% increases to 68. Therefore, although the binding of individual sugars can be easily reversed by thermal energy, there is sufficient strength to create a moderately dense sugar layer on the surface of the NFC, which may help maintain the appropriate mechanical and morphological properties of the NFC after freeze-drying.

[0129] There is a strong correlation between the free energy of sugar bonds and their complexity. The number of hydrogen bonds (HBs) formed between the sugar and the NFC surface was calculated. The number of HBs was highest for lactose, saccharose, and trehalose, and correlates not only with the ability to bind to the NFC surface but also with the number of chemical groups capable of forming hydrogen bonds.

[0130] Figures 8A and 8B show simulation results regarding the induced free energy for cellulose. Various amino acids tested (glycine, leucine, tryptophan, and glutamine) improved the adsorption capacity of saccharose to cellulose. Figure 8B shows the same results as Figure 8A for comparison with tryptophan. Tryptophan has a significantly higher adsorption capacity than saccharose.

[0131] As shown in Figures 9A and 9B, sugar-cellulose hydrogen bonds appear to have increased with amino acids (but not glycine). Glutamine was not adsorbed to cellulose, but tryptophan and glutamine shared numerous hydrogen bonds with cellulose.

[0132] Example 4: FDingEV for long-term storage in an NFC matrix Preliminary results showed that FDed EV containing trehalose, glycine, and sucrose was protected from damage caused by freeze-drying (FDing). FTIR spectra (Figure 10) show that only slight changes occurred in the protein structure of FDed EV when trehalose, sucrose, and glycine were used as cryoprotectants.

[0133] Example 5: FDing 3D cell spheroids for long-term storage in an NFC matrix [Table 2]

[0134] Thirdly, single cells and 3D cell spheroids were freeze-dried with NFC and excipient formulations, and cell viability and morphology were studied. Although no fully viable cells were recovered, the enzymatic activity of FDed 3D cell spheroids was partially conserved (Figure 11). Furthermore, the 3D structure of FDed cell spheroids was conserved (Figure 12), and most importantly, the cytoskeleton of cell spheroids was conserved after FDing and reconstitution (Figure 13) when trehalose and glycine were used as excipients.

[0135] Figure 11 shows FDed and reconstituted 3D cell spheroids stained with a live / dead dual staining kit. Enzyme activity is partially conserved (green), but the cell membrane is damaged and the cells are not completely viable (red).

[0136] Figure 12 shows scanning electron microscope (SEM) images of A) and B) the regular porous structure of FDed NFC aerogel containing 3D cell spheroids, C) 3D cell spheroids encapsulated in NFC aerogel with preserved 3D structure and morphology, and D) 3D cell spheroids encapsulated in NFC aerogel with intact cell membranes. The highly porous and interconnected pores of the NFC aerogel are clearly visible.

[0137] Figure 13 shows the cytoskeleton, F-actin (green), and cell nucleus (blue) of the positive control (left) and FDed and reconstituted 3D cell spheroids (right). The cytoskeleton (F-actin) structure of the FDed cell spheroid was preserved in formulation 1.

[0138] Example 6: Materials and methods used in the example Method used FDing was performed using LyoStarII (SP Scientific). Glass transition temperature and melting point were analyzed by differential scanning calorimetry (DSC, TA instrument). Osmolality of NFC formulations was analyzed using Osmomat 3000 (Gonotec). Viscosity, loss modulus, and storage modulus were studied using a viscometer (Thermo Scientific). Residual water content was measured using a Karl Fischer titrator (Mettler Toledo). MD simulations were performed to study the dynamic behavior of the system and gain insights into specific mechanisms. Morphology of FDed NFC samples and 3D cell spheroids was analyzed using a scanning electron microscope (SEM, FEI Company). The viability of 3D cell spheroids was analyzed by staining cells with a live / dead dual staining kit and analyzing the samples with a confocal microscope (Leica). The skeletal structure of 3D cell spheroids was studied by staining actin with phalloidin-Alexa 488, staining the cell nucleus with DAPI, and imaging the 3D cell spheroids with a confocal microscope (Leica). The metabolic activity of 3D cell spheroids was evaluated using the AlamarBlue assay and VarioskanLux (Thermo Scientific). The number and concentration of FDed EVs were studied using nanoparticle tracking analysis (NTA, Malvern). Protein conservation and protein / lipid ratio of EVs were evaluated using FT-IR (Mettler Toledo). The functionality of FDed EVs was studied using cell viability assays.

[0139] Example 7: Optimization of the lyophilization protocol for nNFC hydrogels The study began with 26 different NFC formulations, and based on the results of previous experiments, the number was reduced to two using a control before the final rheological measurements. The Tg' temperature of all 26 formulations was measured, and freeze-drying was performed on those with a Tg' above -50°C, including the control. The appearance of the cakes was analyzed, and any disintegrated material was removed. Formulations with an osmotic pressure exceeding 450 mOsmol / kg before freeze-drying and after reconstitution were discarded. Three formulations were selected for rheological measurements, and for the three formulations, the loss modulus and storage modulus were analyzed against the last two formulations with optimal properties and the control.

[0140] PC3 protocol: GrowDex 1.5% was diluted to 1.0% in F-12K medium with a PC3 cell concentration of 800,000 cells / ml (80,000 cells / well) supplemented with 10% FBS. 100 μl of GrowDex-media-cell suspension was inoculated into a low-adhesion well plate, and 100 μl of fresh F12K medium supplemented with 10% FBS was pipetted onto the hydrogel mixture. Cells were incubated at 37°C with 5% CO2.

[0141] Lyophilization protocol: In FDing, the samples were first frozen to -55°C at 1°C / min and held at -55°C for 2 hours. Next, the pressure in the FDing chamber was reduced to 100 mTorr, the EV temperature was increased to -40°C, and the temperature of the NFC matrix and cell samples was increased to -50°C (primary drying). After primary drying, secondary drying was initiated. Secondary drying was performed by increasing the shelf temperature from -40°C / -50°C to room temperature at 1°C / min. The vials were closed under reduced pressure and a dry nitrogen atmosphere. The FDing cycle continued for approximately 20 hours for the EV and approximately 48 hours for the NFC matrix and cells. An example of the FDing cycle is shown in Figure 14.

[0142] Those skilled in the art will see that, with advances in technology, the basic concepts may be implemented in various ways. Therefore, the embodiments are not limited to the examples described above, and instead, they may be modified within the scope of the claims.

[0143] The embodiments described herein may be used in any combination of any kind. Several embodiments may be combined together to form further embodiments. The methods, products, or uses disclosed herein may include at least one of the embodiments described herein. It will be understood that the above effects and benefits may relate to one embodiment or to several embodiments. Embodiments are not limited to solving any or all of the problems described or having any or all of the effects and benefits described. Furthermore, it will be understood that references to items preceded by "an" refer to one or more of those items. The term "includes" is used herein to mean including a subsequent feature or action without excluding the presence of one or more additional features or actions.

Claims

1. 1. A method for freeze-drying a hydrogel composition, comprising: providing said hydrogel composition comprising cellulose nanofibrils and / or cellulose nanocrystals, at least one sugar, at least one amino acid and a biologic; and freeze-drying the hydrogel composition to obtain a freeze-dried hydrogel composition.

2. 2. The method of claim 1, wherein the hydrogel composition comprises cell culture medium, the method comprising at least partially removing the cell culture medium from the hydrogel composition and replacing the cell culture medium with a solution comprising the at least one sugar and the at least one amino acid prior to freeze-drying the hydrogel composition.

3. 3. The method of claim 1 or 2, wherein the content of the at least one saccharide in the hydrogel composition before lyophilization is in the range of 100-1000 mM or 150-500 mM.

4. 2. The method of claim 1, wherein the content of the at least one amino acid in the hydrogel composition before lyophilization is in the range of 50-700 mM or 100-500 mM.

5. A freeze-dried hydrogel composition comprising cellulose nanofibrils and / or cellulose nanocrystals, at least one sugar, at least one amino acid and a biological agent, wherein the residual water content of the freeze-dried hydrogel composition is 5 wt% or less.

6. 6. The method of claim 1 or the freeze-dried hydrogel composition of claim 5, wherein the at least one amino acid comprises glycine, leucine, isoleucine, alanine, tryptophan, asparagine, glutamine and / or mixtures or combinations thereof.

7. 10. The method of claim 1 or the freeze-dried hydrogel composition of claim 5, wherein the at least one saccharide comprises at least one of a disaccharide, a trisaccharide, an oligosaccharide, a mixture thereof, or a combination thereof.

8. 10. The method of claim 1 or the freeze-dried hydrogel composition of claim 5, wherein the at least one sugar comprises at least one of sucrose, trehalose, lactose, mixtures thereof, or combinations thereof.

9. 6. The method of claim 1 or the freeze-dried hydrogel composition of claim 5, wherein the content of the at least one saccharide in the freeze-dried hydrogel composition is in the range of 15-80 mol %.

10. 6. The method of claim 1 or the freeze-dried hydrogel composition of claim 5, wherein the content of the at least one amino acid in the freeze-dried hydrogel composition is in the range of 15-60 mol %.

11. 6. The method of claim 1 or the freeze-dried hydrogel composition of claim 5, wherein the ratio of the content of the at least one saccharide to the content of the at least one amino acid in the hydrogel composition and / or the freeze-dried hydrogel composition is in the range of 10:1 to 1:

5.

12. 6. The method of claim 1 or the freeze-dried hydrogel composition of claim 5, wherein the biological preparation comprises a cell, a tissue or a part thereof, an organoid, a micro-organ, a cellular component, an extracellular vesicle, a viral particle, and / or a lipid nanoparticle or lipid-based delivery vehicle, or is a cell, a tissue or a part thereof, such as a spheroid, an organoid, a micro-organ, a cellular component, an extracellular vesicle such as an exosome, a viral particle, and / or a lipid-based delivery vehicle.

13. 10. The method of claim 1 or the freeze-dried hydrogel composition of claim 5, wherein the residual water content of the freeze-dried hydrogel composition is less than or equal to 4 wt%.

14. 10. A method of reconstituting a lyophilized hydrogel composition, comprising adding water or an aqueous solution to the lyophilized hydrogel composition of claim 5.

15. 15. The method of claim 14, wherein the aqueous solution comprises or is at least one of a buffer, saline, cell culture medium, a mixture thereof, or a combination thereof.

16. A reconstituted hydrogel composition comprising nanofibrils and / or nanocrystals, at least one saccharide, at least one amino acid, and a biologic.